The Influence of Ultrasonic Melt Treatment on Microstructural Evaluation of the Al7Si2.5Cu Alloy for Semisolid Processing - Luis Vanderlei Torres; João Paulo de Oliveira Paschoal; Luciano Augusto Lourençato; Eugênio José Zoqui (Materials Research)
Obtaining a refined microstructure is the first step for using it in thixoforming processes. However, the chemical refining of the grain of aluminum alloys with high silicon content is impaired; therefore, grain refining via UST (Ultrasonic Melt Treatment) is a possible solution for these cases. This work aims to analyze the microstructural stability of the microstructure of the Al7Si2.5Cu alloy in the semisolid state. The material was prepared by conventional casting and submitted to processing via UST for 20 seconds with a steel horn. The material underwent reheating heat treatment for 0, 30, 60, 90, and 210 seconds under two solid fractions of 45% and 60%, respectively, 572 and 565 °C. The results show an average primary globule size of around 88 μm and a circularity form factor above 0.50. Regarding the eutectic morphology, it was quite fragmented when processed via UST; that is, the application of acoustic waves in the liquid metal causes it to mix effectively, and it is also capable of breaking the coarser Si particles. When comparing the microstructural evolution of the Al7Si2.5Cu alloy via UST with the ultra-grain refining technique, UST presents superior results in all analyzed scenarios.